Which is the simplified form of the expression (6^-2•6^5)^-3

Question

Which is the simplified form of the expression (6^-2•6^5)^-3

in progress 0
Aaliyah 1 day 2021-10-12T13:23:18+00:00 2 Answers 0

Answers ( )

    0
    2021-10-12T13:24:23+00:00

    Answer:

    1

    Step-by-step explanation:

    ( {6}^{ - 2}  \times  {6}^{5} ) ^{ - 3}  \\  = ( {6}^{3} )^{ - 3}  \\  =  {6}^{0}  \\  = 1

    0
    2021-10-12T13:24:46+00:00

    Answer:

    6^0

    Step-by-step explanation:

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )